Development and Evaluation of Hesperidin-loaded Ethosomal Gel for Wound Healing - Dr. Keshav Bansal, (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Wound healing is a process that restores and regenerates the injured tissues. Polyphenols (Hesperidin) show wound healing properties, but their effective topical application for skin wound healing is challenging due to issues with low loading capacity and delivery efficiency. Ethosomes (lipid-based vesicles) have overcome such problems and emerged as a promising delivery system for improving drug encapsulation and penetration through the skin. Materials and Methods: Hesperidin-loaded ethosomes were formulated with 30% ethanol and analyzed for particle size and shape, encapsulation efficiency, and surface charge. Ethosomes gel was then formulated with 1% w/v Carbopol 934K. Further Hesperidin-loaded ethosomal gel was evaluated for various parameters such as organoleptic properties, pH, viscosity, and skin permeation. An in-vitro wound healing assay was performed to assess the angiogenic properties of Hesperidin-loaded ethosomal gel along with its comparison with pure Hesperidin. Results: The formulated ethosomes were found to have a spherical shape, a vesicle size of 417.9 nm, an entrapment efficiency of 87.32%, and a surface charge of −26.62 mV. The ethosomal gel showed an optimal pH of 5.7, good spreadability, and a release of 86.21%. It has shown stability over 60 days. In-vitro assay revealed that both Hesperidin-loaded ethosomal gel and powder exhibited angiogenic effects, significantly promoting angiogenesis in HaCaT cells over time. Conclusion: The development of Hesperidin-loaded ethosomal gel has successive delivery and addressed the challenges of high loading capacity and effective skin permeation. The results suggest that Hesperidin-loaded ethosomal gel is an effective method for enhancing wound healing through improved delivery.